Flammability assessment of Mediterranean forest fuels - Dimitrakopoulos, A P; Papaioannou, K K (Fire Technology, 2001)
The time-to-ignition of variousdominant Mediterranean forest fuelswasmeasured during laboratory tests, in order to develop a relative ﬂammability classiﬁcation and determine the moisture of extinction of these fuels. The tests were performed with an ignition apparatusmanufactured according to the ISO standards(ISO 5657-1986E) and under a wide gradient of fuel moisture contents, ranging from air-dry to fresh foliage. Moisture content was the single most signiﬁcant factor that affected fuel ﬂammability. Regression modelswere developed between the time-to-ignition and the moisture content valuesof all the fuels tested, and subsequently, were used for the relative ﬂammability ranking of these fuels. Fuel moisture of extinction was assessed to have a threshold value ranging from 40% to more than 140% o.d.w. for the species tested. The ﬂammability ranking of natural fuels can be useful in fuel hazard assessment and ﬁre danger rating, thus facilitating the judicial ﬁre management planning in wildlandsand at the rural-urban interface.
Keywords: flammability; ignitability; Mediterranean; natural fuels; wildland fires